2019
DOI: 10.33073/pjm-2019-044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hepatitis B Virus in Turkish Cypriot

Abstract: There is an increased demand for molecular and epidemiological information regarding Hepatitis B Virus (HBV) infection as the disease severity depends on these specifications. We have aimed to analyze nucleos(t)ide analogues (NA) resistance and typical HBsAg escape mutations with the dispersion of HBV genotype/subgenotype/HBsAg serotypes on overlapping pol/S gene regions in the Turkish population. Samples were collected in Northern Cyprus. Reverse transcriptase (rt) region between 80–250 amino acids were ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In addition, the current study revealed that all HBV samples relevant to serotype ayw2 depend on HBsAg amino acids present at specific loci [ 13 ]. Other studies conducted in Iran and Turkey have shown the dominance of this serotype among the tested HBV samples [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the current study revealed that all HBV samples relevant to serotype ayw2 depend on HBsAg amino acids present at specific loci [ 13 ]. Other studies conducted in Iran and Turkey have shown the dominance of this serotype among the tested HBV samples [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 90%
“…This result appears plausible considering the previous evidence of genotype D dominance in the Eastern Mediterranean region [ 55 , 77 , 78 ]. Genotype D was previously reported to be the most dominant variant of HBV in Iran, Iraq, Syria, Jordan, Lebanon, Palestine, Turkey, and Northern Cyprus [ 46 , 50 , 53 , 79 , 80 , 81 ]. In Iran, two separate studies by Aghakhani et al and Pourkarim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Sumer and Sayan suggested that the HBV genetic diversity seen in Northern Cyprus can be related to the relatively large fraction of students and workers present there, with similar evidence by Arıkan et al . [ 53 , 88 ]. An important point to be considered in areas with extensive genetic diversity of the virus is the higher possibility of recombination, which might yield novel viral variants, that may impact the prophylaxis, diagnosis, and treatment of the disease [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the World Health Organization reported that there were 275 million of people who live with hepatitis B virus and that 887,000 deaths were estimated from this infection, 4,5 which is why it constitutes a public health problem. Prevalence in this study was 0.2 % of blood donors who tested positive for surface antigen and HBV core antibodies (anti-HBc), with 2.1 % reactivity to anti-HBc alone, which is higher than that found in Brazilian donors in 2003 and 2016, which was 0.14 % for anti-HBc and HBsAg, 1.67 % for anti-HBc alone 6 and 1.63 for HbsAg alone.…”
Section: Discussionmentioning
confidence: 99%